Parkinson’s disease physiopathology—beyond the α-synuclein aggregation: a narrative review - Macedo, Victor Fellipe Bispo; Macedo, Vanessa Karine Bispo; de Miranda Coelho, Jorge Artur Peçanha; de Melo Barboza, Alana Madeiro (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is traditionally defined by dopaminergic degeneration and α-synuclein aggregation. However, mounting evidence supports a multifactorial and systemic pathophysiology that extends beyond the central nervous system. This narrative review explores the interconnected mechanisms underlying sporadic PD, including environmental exposures, gut dysbiosis, α-synuclein pathology and propagation, systemic and neuroinflammation, metabolic dysfunctions (notably insulin and lipid metabolism), sleep disturbances, glymphatic impairment, and proteostatic failure.ResultsThe review highlights how α-synuclein pathology can originate peripherally, particularly in the enteric nervous system, and propagate to the brain via neuronal or hematogenous routes. It also examines the synergistic roles of systemic inflammation, immune dysregulation, mitochondrial dysfunction, and impaired protein clearance in promoting neurodegeneration.ConclusionCollectively, these findings support a reconceptualization of PD as a systemic neurodegenerative disorder involving complex crosstalk between peripheral and central pathways. Understanding these multifaceted interactions opens new avenues for early diagnosis, biomarker discovery, and disease-modifying therapeutic strategies targeting the gut-brain axis, metabolic homeostasis, and proteostasis.